Technology of efficient energy utilization the report of a NATO Science Committee Conference held at Les Arcs, France, 8th-12th October 1973 - Kovach, Eugene G. (Pergamon Press, 1974)
Technology of Efficient Energy Utilization is a report of a NATO Science Committee conference held in Les Arcs, France on October 8-12, 1973. The focus of said conference is on energy conservation, the end-uses of energy, and its determining factors in the long run. The report is composed of two parts. Part I includes the working reports from different groups every chapter. The reports cover industrial, residential, and commercial heat; light; motion; electronic and electrolytic processes; and residential, commercial, industrial, urban systems. Part II is the research portfolio, which is divided into three broad groups for easier access: group A – industrial process, group B – transport, and group C – buildings. The text is for those in departments and institutions that study energy and energy conservation, especially those who seek to improve the use of energy.--Provided by publisher.